Selective morphological and volumetric alterations in the hippocampus of children exposed in utero to gestational diabetes mellitus. Issue 8 (25th March 2021) - Lynch, Kirsten M.; Alves, Jasmin M.; Chow, Ting; Clark, Kristi A.; Luo, Shan; Toga, Arthur W.; Xiang, Anny H.; Page, Kathleen A.
Abstract: Prior epidemiological studies have found that in utero exposure to gestational diabetes mellitus (GDM) is associated with increased risk for neurodevelopmental disorders. However, brain alterations associated with GDM are not known. The hippocampus is pivotal for cognition and emotional regulation. Therefore, we assessed relationships between in utero exposure to GDM and hippocampal morphology and subfield structure during childhood. One hundred seventeen children aged 7–11 years (57% girls, 57% exposed to GDM), born at Kaiser Permanente Southern California, participated in the BrainChild Study. Maternal GDM status was determined from electronic medical records. Children underwent brain magnetic resonance imaging. Freesurfer 6.0 was used to measure hippocampal and individual hippocampal subfield gray matter volume (mm 3 ). Morphological analyses on the hippocampal surface were carried out using shape analysis. GDM‐exposed children exhibited reduced radial thickness in a small, spatially‐restricted portion of the left inferior body of the hippocampus that corresponds to the CA1 subfield. There was a significant interaction between GDM‐exposure and sex on the right hippocampal CA1 subfield. GDM‐exposed boys had reduced right CA1 volume compared to unexposed boys, but this association was no longer significant after controlling for age. No significant group differences were observed in girls. Our results suggest that GDM‐exposure impacts shape of the left hippocampal CA1 subfield in both boys and girls and may reduce volume of right hippocampal CA1 only in boys. These in‐depth findings illuminate the unique properties of the hippocampus impacted by prenatal GDM‐exposure and could have important implications for hippocampal‐related functions. Abstract : We sought to investigate the influence of in utero exposure to gestational diabetes mellitus (GDM) on hippocampal morphology and subfield volume in a cohort of children between the ages of 7 and 11 years. We found GDM exposure was associated with reduced radial thickness of the left inferior hippocampal body. We also found a significant interaction between GDM exposure and sex in the right whole hippocampus and CA1 subfield volumes.